Regeneration of highland papaya (Vasconcellea pubescens) from anther culture. (24th September 2018) - Chong‐Pérez, Borys; Carrasco, Basilio; Silva, Herman; Herrera, Francisca; Quiroz, Karla; Garcia‐Gonzales, Rolando
Abstract : Premise of the Study: Vasconcellea pubescens is an important Caricaceae species cultivated in several countries of South America. The objective of this study was to investigate different media compositions and plant growth regulators to induce plant regeneration. Methods: Anthers were cultured in Murashige and Skoog medium with varying concentrations of naphthalene acetic acid (NAA) and 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) plus a cytokinin (N‐(2‐chloro‐4‐pyridyl)‐N′‐phenylurea). The effect of the basal medium supplemented with auxins and cytokinins on shoot regeneration from the induced calli was also evaluated. Addition of maltose to the basal medium was also tested. Results: The combination of 0.54 μM NAA and 22.66 μM 2, 4‐D induced the highest rate of calli formation. Regeneration via organogenesis was obtained in Murashige and Skoog and Woody Plant Medium supplemented with maltose and containing 8.88 μM 6‐benzylaminopurine, 5.71 μM indoleacetic acid, and 2.28 μM zeatin. Discussion: The plant regeneration protocol reported here permits the development of haploid and double haploid plants that can be useful for propagation purposes, allow a better molecular understanding of the species, and facilitate the production of new cultivars.